CONTROLLING AND MONITORING OF TEMPERATURE SYSTEM FOR LIVESTOCK - M. Saleem Khan; Z. Ahmed; M. W. Ashraf; S. Yasmeen; M. Imran; F. Baig; N. Yaseen; S. Jabeen (Journal of Animal and Plant Sciences, 2014)
In this modern era, every passing day reveals a new invention to the world. Every invention gives us new school of thought and with every invention challenges also increase. We can observe and control the system by using the invention of remote control. To control a system automatically, monitoring is mandatory for efficient control. According to changing setup, control is possible by remote monitoring and controlling in livestock, agriculture and food industry. This work is also a part of this chain. We designed and implemented a temperature control and monitoring system for poultry farm at a specific desired temperature. This system consists of temperature sensor LM35, ADC 0804, microcontroller 89S51, fan and LCD for efficient and accurate results of control and monitor as simulation on proteus as well as hardware. This will be feasible for any livestock environment specially poultry farm.
Keywords: Livestock; controlling and monitoring; data acquisition and temperature control